Non-Metallic and Metallic Toxicant Exposures from Personal Care Products in Indonesian Male and Female Medical Students - Putra, Alby Dwinanda; Syamsir, Elmatris; Yulistini, Yulistini; Khaira, Fathiyyatul; Asri, Ennesta; Ilmiawati, Cimi (Majalah Kedokteran Bandung, 2023)
Students can gain various benefits from their daily personal care products. However, the chemicals contained in these products may have adverse health effects. Regardless the inspection performed by regulatory agencies on these products, the products circulating in the market may still contain toxicants thus may jeopardize their safety for use. This study evaluated toxicant ingredients contained in personal care products used by male and female college students. This study was conducted from September to December 2022 on 23 male and 46 female college students of the Faculty of Medicine, Universitas Andalas, Indonesia. Data were collected using a 69-items validated questionnaire. Results were then presented as a distribution of products used categorized by body areas and potentially toxic metallic and non-metallic ingredients identified from their labels. Female college students used at least 10 personal care products, with a median of 19 products. Male students used at least four products and a median of eight products. Investigation on the label of skin, hair, eye, dental and oral, lips, and nail personal care products demonstrated the presence of metallic and non-metallic toxicants. Five metallic toxicants (aluminum, titanium, zinc, copper, and chromium) and 15 non-metallic toxicants (triclosan, talc, fragrance, parabens, butylated hydroxyanisole, butylated hydroxytoluene, diethanolamine, triethanolamine, butylene glycol, propylene glycol, polyethylene glycol, phthalates, benzophenone-3, acetone, and fluoride) were identified. Thus, numerous toxicants are present in marketed personal care products, and females are exposed more than males to these toxicants. Consumers need to be more critical in their choice of personal care products.